The effects of bacteria-nanoparticles interface on the antibacterial activity of green synthesized silver nanoparticles. (January 2017) - Ahmad, Aftab; Wei, Yun; Syed, Fatima; Tahir, Kamran; Rehman, Aziz Ur; Khan, Arifullah; Ullah, Sadeeq; Yuan, Qipeng
Abstract: Neutralization of bacterial cell surface potential using nanoscale materials is an effective strategy to alter membrane permeability, cytoplasmic leakage, and ultimate cell death. In the present study, an attempt was made to prepare biogenic silver nanoparticles using biomolecules from the aqueous rhizome extract of Coptis Chinensis . The biosynthesized silver nanoparticles were surface modified with chitosan biopolymer. The prepared silver nanoparticles and chitosan modified silver nanoparticles were cubic crystalline structures (XRD) with an average particle size of 15 and 20 nm respectively (TEM, DLS). The biosynthesized silver nanoparticles were surface stabilized by polyphenolic compounds (FTIR). Coptis Chinensis mediated silver nanoparticles displayed significant activity against E. coli and Bacillus subtilus with a zone of inhibition 12 ± 1.2 (MIC = 25 μg/mL) and 18 ± 1.6 mm (MIC = 12.50 μg/mL) respectively. The bactericidal efficacy of these nanoparticles was considerably increased upon surface modification with chitosan biopolymer. The chitosan modified biogenic silver nanoparticles exhibited promising activity against E. coli (MIC = 6.25 μg/mL) and Bacillus subtilus (MIC = 12.50 μg/mL). Our results indicated that the chitosan modified silver nanoparticles were promising agents in damaging bacterial membrane potential and induction of high level of intracellular reactive oxygen species (ROS). In addition, these nanoparticles were observed to induce the release of the high level of cytoplasmic materials especially protein and nucleic acids into the media. All these findings suggest that the chitosan functionalized silver nanoparticles are efficient agents in disrupting bacterial membrane and induction of ROS leading to cytoplasmic leakage and cell death. These findings further conclude that the bacterial-nanoparticles surface potential modulation is an effective strategy in enhancing the antibacterial potency of silver nanoparticles. Graphical abstract: Highlights: Biological synthesis of silver nanoparticles. Surface modification of AgNPs with a biocompatible biopolymer. Modulation of bacteria-nanoparticles interface for enhanced activity. Detail mechanism of antibacterial action.